DAMPAK SOSIAL EKONOMI PROGRAM REVITALISASI KEBUN KELAPA SAWIT DI DESA DALIL KECAMATAN BAKAM KABUPATEN BANGKA: SOCIAL ECONOMIC IMPACTS OF THE PALM OIL PLANTATION REVITALIZATION PROGRAM IN DALIL VILLAGE, BAKAM DISTRICT, BANGKA REGENCY - Yulianto, Andry; Agustina, Fournita; Pranoto, Yudi Sapta (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2020)
Inadequate capital strength, limited marketing reach and lack of access to innovation in plantation technology owned by the community have resulted in less than optimal plantation production. The government then collaborates with large plantation companies, both private and state-owned companies to assist and guide smallholder plantations in a mutually beneficial, whole and sustainable cooperation system through a partnership relationship, one of which is the oil palm plantation revitalization program. Plantation revitalization is an effort to accelerate the development of smallholder plantations through expansion, rejuvenation and rehabilitation of plantation crops supported by investment credit from banks and interest subsidies by the government by involving companies in the plantation business sector as partners in plantation development, processing and marketing of products. This study aims to: (1) Describe the socio-economic impacts received by farmers in the revitalization program before and after the program runs (2) Counting the income contribution from oil palm farming by following a revitalization program to the total income of a farmer family in Dalil Village, Bakam District, Bangka Regency. The research method used is survey methods. The analysis tools used is a descriptive qualitative and microsoft excel. The results showing that of the 6 aspects there were 5 aspects that experienced changes in the socio-economic impact of the oil palm revitalization program. The contribution of revitalization farm to the total family income of 35.44%, this shows less than half of family income is obtained from the revitalization farm.